A Clinicopathological Analysis of 75 Salivary Gland Tumors at Mayo Hospital, Lahore - Mahmood, Hafiz Nasir; Haseeb, Ahmad Abdul; Riaz, Nabeela; Firdous, Saadia; Hanif, Saba; Khan, Shammas Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To describe the clinic-o-pathological pattern of patients presented with salivary gland tumors at Department of Maxillofacial surgery Mayo hospital Lahore during time period of one year from 1st January 2019 to 31st December 2019. Methods: This was a retrospective cross-sectional study conducted at Department of Oral and Maxillofacial Surgery, Mayo Hospital Lahore. 75 cases of Salivary gland tumors in the head and neck region were identified. Patient’s medical record and pathology reports were retrieved and carefully reviewed by a senior doctor to collect basic demographic data as well as tumor related information. Data entry and analysis was done with the help of SPSS version-26. Chi Square Test/Fisher exact test was applied to see the association between qualitative variables. Results: In this study Mean age of patients in this study was 40.45±13.18. Male patients were predominant as compared to female patients; Male 53.3% & Female 46.7%.The most frequent tumor among patients was Pleomorphic Adenoma (61.3%) followed by Adenoid Cystic Carcinoma (17.3%), Mucoepidermoid Carcinoma (13.3%), Warthin’s Tumor (4%), Squamous cell Carcinoma of Parotid (2.7%) and adenocarcinoma (1.3%) respectively. However no significant association was seen between salivary gland tumors with age and gender of patients (p-value=0.521). Conclusion: Among the benign salivary gland tumors pleomorphic adenoma is the most common tumor whereas among malignant salivary gland tumors adenoid cystic carcinoma is the most frequent occurring tumor.